Hermeneutics, deconstruction and nomad sense (2009)
The author deals with the matter of sense, taking as referent two of 20th century's crucial paradigms: Hans Georg Gadamer's Hermeneutics and Jacques Derrida's Deconstruction. He draws up the concept of "nomad sense", which he pretends to be useful to get up to approach the tow philosophers, normally taken as distant and even antagonist, and also to give response to the question about sense, escaping both to nonsense and unique and definite sense unsatisfactory tendencies.